Penguatan Karakter Religius melalui Program Tahfidzul Qur’an: Studi pada Peserta Didik Kelas 4 MI Masalikil Huda 01 Tahunan - Naziyah, Putri Rahma Wati; Amir Gufron (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to explore the implementation of the Tahfidzul Qur’an Program at MI Masalikil Huda 01 Tahunan in shaping the religious character of fourth-grade students and to identify the factors influencing its success. Using a qualitative approach and a descriptive method, this research analyzes the program’s implementation process, the challenges encountered, and its impact on students' character development. The findings indicate that the tahfidz program significantly contributes to improving Qur’anic memorization and fostering religious character, particularly in terms of discipline, noble morals, and steadfastness (istiqamah). However, challenges such as limited parental involvement and the influence of digital devices that reduce students’ focus remain obstacles in its implementation. These findings reinforce character education theories based on religious values, emphasizing the importance of synergy between schools and families in shaping students’ religious character. Therefore, this study recommends increasing parental involvement in guiding Qur’anic memorization at home as a strategy to optimize the success of the tahfidz program.